What Is the Role of AI in Poison Control? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2015)
Poison control centers are essential for managing poisonings, but they face challenges like high call volumes and the need for quick, accurate decisions. Art...
Keywords: AI in Emergency Medicine; Poison; Control; Artificial Intelligence; Machine Learning; Deep Learning; Healthcare